EARLY CLINICAL EFFECTIVENESS OF FASTTRACK TECHNOLOGIES IN TUMORS OF THE FEMALE REPRODUCTIVE SYSTEM - B.S. Muminov (Western European Studies, 2026)
The aim of this study was to evaluate the impact of implementing Fast-track protocols on early postoperative clinical outcomes in patients with tumors of the female reproductive system
Keywords: Fast-track; oncogynecology; tumors of the female reproductive system; perioperative management